Gregarious flowering of Dendrocalamus strictus in Uttar Pradesh and Maharashtra, India: Compared with historical records - Harsh B. Naithani; Rama Kant; Rajendra K. Meena; Maneesh S. Bhandari; Rimpee Garg (Advances in Bamboo Science)
Dendrocalamus strictus, commonly known as Male bamboo or Lathi bans, accounts for approximately 53 % of India’s bamboo-growing area. The species has a flowering cycle ranging from about 25–45 years. In the present article,authors report recent gregarious flowering events in two states, namely Uttar Pradesh and Maharashtra of India. These events are then compared with past historical flowering records and generated database of D. strictus. The present database will be utilized for future genetic conservation, improvement programmes, and management of bamboo genetic resources (BGRs).